(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to assess the level of teacher readiness in implementing E-Learning. This study evaluates eLearning on system usage, user satisfaction, system quality, information quality, and service quality. This study uses a quantitative descriptive method to describe teacher readiness in implementing eLearning. Data was collected by distributing the E-Learning Implementation questionnaire with the Human Organization Technology and Net Benefit (HOT-Fit) model to one hundred and one Vocational High School teacher respondents. Data analysis techniques in this study used descriptive statistical methods. The results showed that the level of teacher readiness on the indicators for using the E-learning system in SMKs was very ready with the system; indicators of user satisfaction are very satisfied with the teacher’s service in facilitating learning. While the level of implementation of system quality indicators used in learning is very feasible, indicators of information quality in Vocational High Schools are. Also, students feel very good about giving information. The story of readiness in implementing teacher service quality during learning is very satisfying. Of the five indicators considered to measure teachers’ readiness level in Vocational High Schools, information quality gets the best rating because the government supports all. Overall, teachers are very prepared to implement E-Learning. Based on the standard index of teacher readiness, it is at an optimal level. These results conclude the readiness level of Vocational High School teachers. Very ready to implement E-Learning by fulfilling all wishes on indicators of system use, user satisfaction, system quality, information quality, and service quality.